Indonesia Market Study : Movable Assets-Based Financing to Micro, Small, and Medium Enterprises - International Finance Corporation (International Finance Corporation, Washington, DC, 2016)
The report aims to assess the current market for movable assets based lending with respect to micro, small and medium enterprises (MSMEs) in Indonesia. The sections of the report highlight the addressable demand for MSMEs and the current supply provided by various formal sources of financing in Indonesia. Traditionally, financial institutions have preferred lending against fixed asset collateral only. Using that as a starting point, the report seeks to identify the current challenges in lending against movable assets. It further extends the need for a greater financial infrastructure that can facilitate the ability of lenders to evaluate risks in movable assets based lending. This report delves into the lending challenges faced by MSMEs as well as the challenges that restrict greater supply of credit by financial institutions. It draws on data and insights based on discussions with over 70 financial institutions in Indonesia, and an understanding of the credit requirements of MSMEs – based on over 850 sample cases for quantitative data. These findings were further examined through in-depth qualitative discussions with 34 MSMEs spread across multiple regions in Indonesia. As the Indonesian economy follows a traditional model of providing credit based on fixed collateral, such as land and buildings, the study focuses on: (i) understanding the current credit demand that can be potentially addressed by movable assets to complement the traditional model, and (ii) the challenges that need to be addressed to facilitate the ensuing movable assets based lending.